Relationship between molecular conversions of acrosin and the progression of exocytosis in the calcium ionophore-induced acrosome reaction - Moos, J; Peknicova, J; Tesarik, J (Biochimica et biophysica acta, 1993)
In this study we used a previously characterized monoclonal antibody to analyze the molecular conversions of acrosin during the acrosomal exocytosis induced by ionophore A23187. Before sperm exposure to the ionophore, most of the sperm acrosin was in the form of proacrosin (55-kDa and 53-kDa forms). Upon exposure to the ionophore, the concentration of proacrosin in sperm samples decreased rapidly and was negatively correlated with the progression of exocytosis. After 1 h of ionophore treatment, proacrosin was quantitatively converted into the two active acrosin forms, alpha-acrosin (49 kDa) and beta-acrosin (36 kDa). However, products of further acrosin conversions were not found after this treatment. As compared with the speed of acrosin activation during sperm contact with the ionophore, the ionophore-induced release of acrosin from the sperm cells into the soluble fraction was apparently delayed, and only the active acrosin forms (49 kDa and 36 kDa) were found in sperm incubation media. External Ca2+ influenced the speed of proacrosin conversion in a concentration-dependent manner. The ionophore-induced activation of proacrosin and acrosome reaction were partially inhibited by trypsin inhibitors. The results suggest that proacrosin activation is an essential step in the mechanism of the acrosomal exocytosis.
Keywords: Animals; akrosin; Enzyme Precursors; spermie; Calcimycin; Spermatozoa; prasata; vápník; Exocytosis; inhibitory trypsinu; Calcium; Male; Swine; exocytóza; Trypsin Inhibitors; calcimycin; zvířata; mužské pohlaví; Acrosin; prekurzory enzymů